IBM Storage Networking c-type FICON Implementation Guide - White, William; Applewhaite, Aubrey; Blair, Mike; Fisher, Gary; O'Reilly, Gavin; Ramsey, Lyle; Vaninetti, Fausto (IBM Redbooks, 2022)
The next-generation IBM® c-type Directors and switches for IBM Storage Networking provides high-speed Fibre Channel (FC) and IBM Fibre Connection (IBM FICON®) connectivity from the IBM Z® platform to the storage area network (SAN) core. It enables enterprises to rapidly deploy high-density virtualized servers with the dual benefit of higher bandwidth and consolidation. This IBM Redpaper Redbooks publication helps administrators understand how to implement or migrate to an IBM c-type SAN environment. It provides an overview of the key hardware and software products, and it explains how to install, configure, monitor, tune, and troubleshoot your SAN environment.